2020
DOI: 10.3389/fpsyt.2020.00620
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trazodone on Sleep Quality and Cognitive Function in Arteriosclerotic Cerebral Small Vessel Disease Comorbid With Chronic Insomnia

Abstract: Background Chronic insomnia is common in patients with arteriosclerotic cerebral small vessel disease (CSVD) and aggravates the cognitive impairment caused by CSVD. Low-dose trazodone is effective in treating insomnia, but it is unclear whether it can also improve cognitive function in CSVD patients. This study was performed to explore the effects of trazodone on sleep quality and cognitive function in CSVD comorbid with chronic insomnia. Methods This was a randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…The rightmost columns of Tables 1 and 2 display the ultimate effect of trazodone on human cognition. Overall, from the 16 studies included, seven showed no effect of trazodone on human cognition [ 7 , 9 , 14 , 15 , 17 19 ], while five showed a positive effect by improving cognition or reducing cognitive decline [ 6 , 10 12 , 16 ], and four showed a negative effect by impairing cognitive function [ 8 , 13 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The rightmost columns of Tables 1 and 2 display the ultimate effect of trazodone on human cognition. Overall, from the 16 studies included, seven showed no effect of trazodone on human cognition [ 7 , 9 , 14 , 15 , 17 19 ], while five showed a positive effect by improving cognition or reducing cognitive decline [ 6 , 10 12 , 16 ], and four showed a negative effect by impairing cognitive function [ 8 , 13 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies demonstrated the effects of trazodone in domains other than cognitive function. Wang et al, Alikhani et al, Camargos et al, and Roth et al all showed that trazodone improved sleep quality and sleep parameters including sleep efficiency, N3 sleep ratio, and sleep continuity [ 6 ], daytime functioning [ 12 ], and nighttime sleep percent [ 17 ], while not inducing [ 12 , 17 ] or decreasing daytime sleepiness [ 6 , 20 ], reducing nighttime awakening [ 20 ], minutes of stage 1 sleep, or self-reports of trouble sleeping [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations